Question
upstudy study bank question image url

Solve for \( n \) \[ \begin{array}{c}6 n-7(n+1)=6 n \\ n=\square \\ \text { Submit }\end{array} \]

Ask by Wells Ellis. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( n = -1 \)

Solution

Solve the equation \( 6n-7(n+1)=6n \). Solve the equation by following steps: - step0: Solve for \(n\): \(6n-7\left(n+1\right)=6n\) - step1: Cancel equal terms: \(-7\left(n+1\right)=0\) - step2: Change the sign: \(7\left(n+1\right)=0\) - step3: Rewrite the expression: \(n+1=0\) - step4: Move the constant to the right side: \(n=0-1\) - step5: Remove 0: \(n=-1\) The solution to the equation \(6n-7(n+1)=6n\) is \(n=-1\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve for \( n \), we start with the equation: \[ 6n - 7(n + 1) = 6n \] First, distribute the \(-7\) on the left-hand side: \[ 6n - 7n - 7 = 6n \] Now, combine like terms: \[ - n - 7 = 6n \] Next, add \( n \) to both sides to get all terms involving \( n \) on one side: \[ - 7 = 6n + n \] This simplifies to: \[ - 7 = 7n \] Now, divide both sides by \( 7 \): \[ n = -1 \] Thus, the solution is: \[ n = -1 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy